2009
DOI: 10.1111/j.1751-7176.2009.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control in Hypertensive Patients in Irish Primary Care Practices

Abstract: In Ireland, cardiovascular disease is a major cause of death. However, blood pressure (BP) goal achievement is unsatisfactory. The authors aimed to document BP control and increase awareness. A total of 1534 patients were enrolled in the study, with a mean age of 64.7±11.9 years (53.8% women). Duration of hypertension was 8.7±7.7 years, and 14.6% had diabetes, 13.8% had coronary artery disease, and 40.5% were taking antihypertensive monotherapy. β‐Blockers (39.8%), angiotensin‐converting enzyme inhibitors (32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
9
2
Order By: Relevance
“…An Irish survey found BP controlled in 48.6% of primary health care patients while study based on United States national health and nutrition examination survey (2001)(2002) have reported BP control in 53.1% of hypertensive patients. [19][20][21] Majority of the patients were in their middle age. There were more male patients than female.…”
Section: Discussionmentioning
confidence: 99%
“…An Irish survey found BP controlled in 48.6% of primary health care patients while study based on United States national health and nutrition examination survey (2001)(2002) have reported BP control in 53.1% of hypertensive patients. [19][20][21] Majority of the patients were in their middle age. There were more male patients than female.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[19][20][21] International reports including the United States National Health and Nutrition Examination Survey (2001-2002) 22,23 reported BP control in 53.1% of hypertensive patients, while an Irish survey 24 found BP control in 48.6% of PHC patients. Achieving BP control in 57% of patients in a less resourced PHC setting suggests that PHC has the potential to play a pivotal role in the control of CV diseases in South Africa, since hypertension is the largest contributor to CV diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with other findings in the voluntary Swedish National Diabetic Register 30 and elsewhere. 31 Furthermore, high-risk patients often need to be given two or more antihypertensive drugs in order to reduce blood pressure to target. 32,33 We found that 71% did not have a target blood pressure when given monotherapy.…”
Section: Discussionmentioning
confidence: 99%